Comparison of the Structure of Spiral and Lenticular Galaxies, NGC 4305 and NGC 4203 as a Sample: Astronomy And Space Department, College of Sciences, University of Baghdad, Baghdad, Iraq - Ahmed, Abdullah K (Iraqi Journal of Science, 2023)
Photometric techniques are one of the fundamentals and of great importance in the study of astronomical phenomena, including galaxies, and has witnessed a wide development during the last 100 years in equipment, sensitivity and accuracy in data analysis, especially after the direction toward space telescopes and the widespread use of a CCD camera. Therefore, in this research, an analytical study will be made to compare two types of galaxies, which are spiral and lenticular galaxies, using photometric techniques and compare the photometric parameters of each type with tables and illustrations. An analysis of the morphological of the two galaxies was done by using the Least Square Fitting Method, and it was fully explained in the research. The results showed the clear difference between the structure of spiral and lenticular galaxies.